Implementation of Islamic Religious Education Learning for Children With Special Needs in Inclusive Schools: A Case Study of State Elementary School 003 Bontang Utara - Ridwan; Andi Fitriani Djollong; St Wardah Hanafie Das; Andi Abdul Muis (EDUJAVARE: International Journal of Educational Research, 2026)
Islamic Religious Education (PAI) in inclusive schools faces particular challenges because it must remain accessible to students with special needs (ABK) who have diverse learning characteristics. This study aims to analyze the planning, implementation, and evaluation of PAI learning for ABK at SD Negeri 003 Bontang Utara, a public elementary school that organizes inclusive education. The study employed a qualitative case study design. Data were collected through participatory observation, in-depth interviews with PAI teachers, special assistant teachers, and the school principal, and document study of learning instruments, then analyzed following the Miles, Huberman, and Saldaña model reinforced with Yin's pattern-matching technique, with credibility established through source and technique triangulation and member checking. The findings show that PAI lesson planning is carried out adaptively through individual needs identification, modification of objectives into functional outcomes, simplification of materials, selection of concrete media, and preparation of socio-emotional strategies synchronized with the Individual Learning Program. Implementation takes place inclusively and collaboratively through mixed classrooms, peer tutoring, positive reinforcement, and persuasive behavior management. Evaluation is authentic, individual, and process-based, emphasizing gradual progress in worship practice, social behavior, and independence rather than comparison with regular students' standards. These findings align with Law Number 8 of 2016, Ministerial Regulation Number 48 of 2023, and the Qur'anic value of human equality. The study recommends strengthening PAI teachers' competence in inclusive learning and developing a more systematic PAI differentiation guideline for inclusive elementary schools.